Peningkatan Penanaman Tomat di Desa Bahalbatu III Kecamatan Siborongborong (International Forum of Researchers and Lecturers, 2024)
Tomatoes are a fruit that is very easy to find in Indonesia. Tomatoes are much loved by the public. Apart from having a delicious taste, they also contain lots of nutrients and vitamins in the fruit. Based on research results, this journal explores increasing knowledge of how to plant tomatoes properly, including how to caring for tomatoes from seeding to harvest so as not to cause crop failure in tomato planting, therefore increasing tomato planting needs to be known by the community to increase the productivity of community agricultural products.